Autoimmune progesterone dermatitis: a retrospective case series - Nessa Aghazadeh; Nicholas A. Berry; Rochelle R. Torgerson; Miguel A. Park; Dawn Marie R. Davis (Wolters Kluwer, 2022)
Background:. Autoimmune progesterone dermatitis (APD) is a rare hypersensitivity disorder characterized by recurring dermatologic manifestations during the luteal phase of the menstrual cycle in women. Well-defined clinical and diagnostic criteria, outcomes measurements, and standard treatments are lacking. Methods:. We performed a single-institution retrospective review of adult patients (older than 20 years at the time of diagnosis) with APD. Results:. Fourteen patients were included with mean age of clinical onset of 34.3 ± 7.7 (range 24-54) years. There was a delay of 3.9 ± 5.5 (range 0.4-20) years between the onset of disease symptoms and diagnosis. The onset of APD was after exposure to exogenous progesterone in 9 of 14 patients. Progesterone skin test was performed in 9 patients and 6 were positive. Patients frequently presented with urticaria (9/14, 64.3%) and dermatitis (4/14, 28.6%). Continuous combined oral contraceptives (4/14, 28.6%), gonadotropin-releasing hormone agonist (3/14, 21.4%), and hysterectomy with bilateral salpingo-oophorectomy (2/14, 14.3%) were the most common attempted treatments with reliable outcomes. Conclusions:. APD is a rare disorder which lacks universal diagnostic measures and criteria, contributing to a significant delay in diagnosis. Large-scale multicenter studies are needed to develop accurate tests, establish diagnostic criteria, and define treatment outcomes.